Respostas
respondido por:
2
Olá!!!!
Resolução!!!
Quadrado da diferança entre dois termos :
Formula :
( a - b )² = a² - 2ab + b²
= ( 5y - 1 )²
= ( 5y )² - 2 • 5y • 1 + 1²
= 25y² - 10y + 1 ← resposta
Espero ter ajudado!!!
Resolução!!!
Quadrado da diferança entre dois termos :
Formula :
( a - b )² = a² - 2ab + b²
= ( 5y - 1 )²
= ( 5y )² - 2 • 5y • 1 + 1²
= 25y² - 10y + 1 ← resposta
Espero ter ajudado!!!
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás